Analisis Dampak Alih Fungsi Lahan Padi Menjadi Lahan Perkebunan Tebu di Desa Pelang Kecamatan Kembangbahu Kabupaten Lamongan - Maya Fita Suwahyuni; Anita Handayani; Wasti Reviandani (Jurnal Mahasiswa Manajemen, 2021)
Background - The people in Pelang Village, Kembangbahu District, Lamongan Regency, the majority of their livelihoods come from the agricultural sector. In 2017-2020 many farmers are converting rice land into sugar cane plantations. The impact of land shifting results in reduced planting and harvested areas for food crops or reduced amounts of rice production and changes in income. Objective - This study aims to determine the income before land conversion, the impact on income after land conversion, the causes of land conversion, and the impacts. Design/Methodology/Approach - This type of research is a qualitative research. The technique used in this research is purposive sampling with structured interviews and unstructured interviews (free). The data used in this study is primary data. Findings - The results of this study indicate that the impact on the income obtained by farmers before transferring land is experiencing stability, while the impact after transferring rice land to sugar cane has increased. The cause of rice farmers who transfer their land to sugar cane farmers because they can get increased profits. Research implications - This research can be used as material for consideration when changing the function of land owned by farmers. Research limitations - This study has limitations regarding the yield generated during harvest. Researchers only get income information every time it is harvested, the income has not been reduced by drugs in the treatment of the land owned.